Improving awareness of energy conservation: Rocky Mountain City. Issue 1 (16th August 2021) - Keller, Sarah; Otjen, A.J.; McNally, Mary; Wilkinson, Timothy J.; Dockery, Brenda; Leonard, Jennifer; Southworth, Hayley
Abstract : Purpose: The purpose of this research project was to improve public awareness to improve public awareness of the importance of energy conservation and to improve the use of simple conservation strategies. A thorough evaluation of the net gain from the numerous energy campaigns rolled out to the public every year is lacking. This study conducted pre- and post-campaign surveys and focus groups to evaluate one campaign's impact on self-reported energy behaviors. Design/methodology/approach: The campaign used television public service announcements and a website to improve awareness of the city's efforts to conserve energy and to increase individual energy conservation practices. Focus groups ( n  = 40) were used to identify common barriers to conservation, and pre- and post-surveys ( n  = 533, 479) were conducted to evaluate the campaign's effectiveness. Findings: Results indicated that the campaign increased positive changes in changing light bulbs and confidence in taking action to turn down thermostats, unplug devices and turn off lights. While follow-up research is needed on the precise mechanism of the psychological process at work, the findings are consistent with the concepts of self and response efficacy as needed components of any behavior change. The authors advocate the adoption of research-informed message design to maximize communication campaign effects. Originality/value: This paper demonstrates how the combination of three prominent persuasion theories can be used to develop behavior change campaigns. Also, it is one of the few studies to evaluate the effectiveness of the Energy Star campaign.